Analisis Literasi Keuangan Mahasiswa dan Kaitannya dengan Pola Perilaku Konsumtif dalam Kehidupan Sehari-hari - Harefa, Menisati; Hadi, Syamsul (Mahesa Research Center, 2025)
This article aims to analyze students’ financial literacy and its relation to their consumption behavior in daily life. The focus is on differences in financial literacy levels among students and their impact on consumption decisions, including psychological, social, and cultural factors that influence behavior. To address this issue, the study draws on theories of financial literacy and consumption behavior. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed qualitatively using thematic analysis. The study concludes that students’ financial literacy levels vary significantly and affect their consumption behavior; students with high financial literacy can control spending and make prudent financial decisions, whereas students with low financial literacy tend to engage in impulsive purchases and prioritize instant gratification. Students with moderate literacy exhibit moderate consumption behavior and are susceptible to external influences. This research emphasizes the importance of developing financial literacy through education, training, and digital platforms to foster financial awareness and sustainable money management habits.